The Effect of Public Accountability, Internal Control and Organizational Commitments on Managerial Performance in the Office of Industry and Trade Serdang Bedagai District - Elwardi Hasibuan (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of Public Accountability, Internal Control and Organizational Commitment on Managerial Performance at the Office of Industry and Trade, Serdang Bedagai Regency . The population as well as the sample in this study amounted to 35 people. The data used in this study are primary data obtained through questionnaires, interviews, field observations and documentation. The results of statistical tests in this study state that the variables of Public Accountability, Internal Control and Organizational Commitment able to affect managerial performance by 26.8% while the remaining 73.2% is influenced by other variables not examined in this study. From the Coefficients table a the multiple linear regression equation Y = 17,297 + 0.086 + 0.013 + 0.904. Constant (a) = 17,297 is positive and the independent variable is positive, which means Public Accountability , Internal Control and Organizational Commitment has a positive relationship to managerial performance.